Hepatocyte‐induced CD4+ T cell alloresponse is associated with major histocompatibility complex class II up‐regulation on hepatocytes and suppressible by regulatory T cells. Issue 3 (23rd February 2018) - DeTemple, Daphne E.; Oldhafer, Felix; Falk, Christine S.; Chen‐Wacker, Chen; Figueiredo, Constanca; Kleine, Moritz; Ramackers, Wolf; Timrott, Kai; Lehner, Frank; Klempnauer, Juergen; Bock, Michael; Vondran, Florian W. R.
Abstract : Hepatocyte transplantation is a promising therapeutic approach for various liver diseases. Despite the liver's tolerogenic potential, early immune‐mediated loss of transplanted cells is observed, and longterm acceptance has not been achieved yet. Patients deemed tolerant after liver transplantation presented an increased frequency of regulatory T cells (Tregs), which therefore also might enable reduction of posttransplant cell loss and enhance longterm allograft acceptance. We hence characterized hepatocyte‐induced immune reactions and evaluated the immunomodulatory potential of Tregs applying mixed lymphocyte cultures and mixed lymphocyte hepatocyte cultures. These were set up using peripheral blood mononuclear cells and primary human hepatocytes, respectively. Polyclonally expanded CD4 + CD25 high CD127 low Tregs were added to cocultures in single‐/trans‐well setups with/without supplementation of anti‐interferon γ (IFNγ) antibodies. Hepatocyte‐induced alloresponses were then analyzed by multicolor flow cytometry. Measurements indicated that T cell response upon stimulation was associated with IFNγ‐induced major histocompatibility complex (MHC) class II up‐regulation on hepatocytes and mediated by CD4 + T cells. An indirect route of antigen presentation could be ruled out by use of fragmented hepatocytes and culture supernatants of hepatocytes. Allospecific proliferation was accompanied by inflammatory cytokine secretion. CD8 + T cells showed early up‐regulation of CD69 despite lack of cell proliferation in the course of coculture. Supplementation of Tregs effectively abrogated hepatocyte‐induced alloresponses and was primarily cell contact dependent. In conclusion, human hepatocytes induce a CD4 + T cell alloresponse in vitro, which is associated with MHC class II up‐regulation on hepatocytes and is susceptible to suppression by Tregs. Liver Transplantation 24 407–419 2018 AASLD.